Soft systems as a helping tool in the assessment of sustainable business practices and risks in a socio-economic-environmental context - Duarte de Almeida, I.; Boas da Silva, J. M.. (Proceedings of the 23rd Cambridge International Manufacturing Symposium, 2019)
Sustainability indicators (SI) are fundamental instruments in business practices towards evaluation of general sustainability, its inherent risks, or the interaction of socioeconomic perspectives in an environmental sustainability context. The complex nature of the models applied call for a revision of the scientific methodologies used in the production of indicators addressing measurability, fitting them to a different nature of the problem characterised by (i) multiple, circular, conflictual relations in a web of heterarchical relations; (ii) the social component relevance; (iii) the existence of an observer bias and interest, stakeholders pressure, interaction with the phenomenon and interpretation, establishing unrepeatable situations that can only be analytically discussed in different contexts. Multi criterion alternatives are advocated and one is briefly characterised: the Soft Systems Methodology (SSM). Its advantages are summarised. The logic and impact of SSM in a classical evaluation process based on the need for feedback are also discussed. The conclusion argues in favour of SSM contribution for scientific knowledge, focusing on validity, in comparison with other methodologies utilised in the Economic, Social, and Environmental Impact Assessment of business practices.